2020
DOI: 10.1007/s10570-020-03400-6
|View full text |Cite
|
Sign up to set email alerts
|

Using microwave irradiation to catalyze the in-situ manufacturing of silver nanoparticles on cotton fabric for antibacterial and UV-protective application

Abstract: Antibacterial and UV-protective cotton fabrics were produced with an in-situ synthesis of silver nanoparticles using trisodium citrate as reductive agent and microwave irradiation for starting the synthesis reaction. The creation of silver nanoparticles with different morphologies such as quasi-spherical and cubic nanoparticles was confirmed by the SEM images. The EDS pattern of the loaded sample confirmed the uniform silver loading on the surface of cotton fibers as well as their crystal structure was approve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 48 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…The NPs seemed to be spherical in SEM pictures. The findings revealed that the NPs finished cotton fabric has a wash fastness of ten washes (Poortavasoly and Montazer 2014;Ullah et al 2014;Barani and Mahltig 2020;Boomi et al 2020;Čuk et al 2021). 20 nm.…”
Section: Scan Electron Microscope (Sem)mentioning
confidence: 99%
“…The NPs seemed to be spherical in SEM pictures. The findings revealed that the NPs finished cotton fabric has a wash fastness of ten washes (Poortavasoly and Montazer 2014;Ullah et al 2014;Barani and Mahltig 2020;Boomi et al 2020;Čuk et al 2021). 20 nm.…”
Section: Scan Electron Microscope (Sem)mentioning
confidence: 99%
“…Cotton fibres are inherently nutritious and hydrophilic and therefore provide an excellent environment for the growth of bacteria and fungi (Ravindra et al 2010), and they do not in themselves have an effective barrier to UV radiation, especially when undyed or dyed in light shades (Czajkowski and Paluszkiewicz 2008). Silver nanoparticles (AgNP) applied on cotton have been found to play an important role in developing protective properties against pathogenic bacteria (Bachir and Abouni 2015;Ibrahim et al 2020;Khalil et al 2014; Barani and Mahltig 2020) and UV radiation (Rao et al 2019;Aladpoosh et al 2014). The application of AgNP on cotton fabrics can be carried out in two-step or one-step processes.…”
Section: Introductionmentioning
confidence: 99%
“…Such changes in the spectrum of AgNP indicate the adsorption of carbonyl groups and imidazolium cations on their surface [23] and the formation of complexes of the "guest-host" type between HB-OIL and silver ions. In addition, there are intense absorption bands at 1418 cm -1 and 1575 cm -1 in the spectrum of AgNP, which are related to symmetric and asymmetric valence vibrations of carboxylate anions of trisodium citrate [24], which partially overlap with such valence vibrations of C-C bonds of the aromatic component and deformational vibrations of C-H bonds of methyl and methylene groups of HB-OIL. This indicates the presence of trisodium citrate adsorbed on the surface of the synthesized AgNP and that formed complexes with silver ions.…”
Section: Results and Their Discussionmentioning
confidence: 99%